The impact of molecular genetic analysis of theVHL gene in patients with haemangioblastomas of the central nervous system. Issue 6 (1st December 1999) - Gläsker, Sven; Bender, Bernhard U; Apel, Thomas W; Natt, Ernst; van Velthoven, Vera; Scheremet, Rudolf; Zentner, Josef; Neumann, Hartmut P H
Abstract : OBJECTIVES: Haemangioblastoma of the CNS occurs as a sporadic entity and as a manifestation of the autosomal dominant von Hippel-Lindau disease with the major additional components retinal angioma, renal cancer, and pheochromocytoma. Genetic testing for germline mutations predisposing to von Hippel-Lindau disease has been available since identification of the VHL tumour suppressor gene. The impact of this testing was evaluated in patients with haemangioblastomas seen in this centre. METHODS: A register and database of patients with symptomatic haemangioblastomas for the last 15 years was evaluated. The VHL gene was analysed by the SSCP method for all exons and Southern blotting for mutations and deletions of the gene. RESULTS: 141 patients with haemangioblastoma of the CNS were registered. In 81 patients (57%) there was a disease predisposing germline mutation including eight novel mutations. Population related calculation of patients from the administrative district of Freiburg disclosed VHL germline mutations in 22% of the patients with haemangioblastoma. Analysis of mutation carriers for clinical information suggestive of the syndrome showed (1) a positive family history of a brain tumour in 50%, (2) a history for the patient of extracranial manifestations in 36% (retinal angioma 30%, pheochromocytoma 6%), and (3) 19% presenting with multiple brain tumours when first admitted. By genetic testing of haemangioblastoma patients without any indications of von Hippel-Lindau disease mutation carriers were identified in 14%. Sensitivity of VHL germline testing was 86%. CONCLUSIONS: DNA analysis for VHL germline mutations is clearly superior to clinical information in the diagnosis of von Hippel-Lindau disease. Although the percentage of von Hippel-Lindau disease associated haemangioblastoma decreases after the fourth decade of life and is infrequent in patients without other symptomatic lesions and a negative family history, it is recommended that every patient with CNS haemangioblastoma should be screened for von Hippel-Lindau disease germline mutations. This provides the key information and enables screening for extraneurological tumours of the patients and investigations of the patient′s family to ameliorate management of von Hippel-Lindau disease.